2020
DOI: 10.3390/catal10020210
|View full text |Cite
|
Sign up to set email alerts
|

Use of Titanium Complexes Bearing Diphenolate or Calix[n]arene Ligands in α-Olefin Polymerization and the ROP of Cyclic Esters

Abstract: In this review, we discuss the use of titanium complexes bearing either bridged diphenolate or calix[n]arene (n = 4, 6, 8) ligation, in the formation of plastics from α-olefins or via the ring opening polymerization (ROP) of cyclic esters. The syntheses, molecular structures and catalytic behaviour of these systems are discussed, as well as where possible, the properties of the resultant polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…173.17 16, O 14-Ti 6-N(4A) 169.60 16, Cl 9-Ti(7)-Cl 10167.29 6, O 15-Ti(7)-N(5A) 173.91 15, O 16-Ti 7-O(19) 164.48 (15). (6•6MeCN).…”
Section: Dalton Transactions Papermentioning
confidence: 99%
See 1 more Smart Citation
“…173.17 16, O 14-Ti 6-N(4A) 169.60 16, Cl 9-Ti(7)-Cl 10167.29 6, O 15-Ti(7)-N(5A) 173.91 15, O 16-Ti 7-O(19) 164.48 (15). (6•6MeCN).…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…We have recently reviewed the use of titanium diphenolates and titanocalix [4]arenes for both α-olefin polymerization and the ROP of cyclic esters. 15…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic systems containing titanium complexes have been applied both for ethylene homopolymerization and its copolymerization with other olefins. [3][4][5] Titanium(IV) complexes can even catalyze the copolymerization of ethylene with olefins functionalized with polar groups, which is a challenging task for early transition metals. [6,7] Recently it was shown that Ti(IV) alkoxide complexes with 1,2-and 1,4-diolate ligands activated by binary activator {Bu 2 Mg + Et 2 AlCl} catalyze the polymerization of ethylene with the formation of ultra-high molecular weight polyethylene (UHMWPE).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, undesired transesterification reactions are promoted by tin octoate, resulting in broad molecular weight distributions. Hence, alternative systems based on different metal/ligand combinations, capable of better control over the polymerization process, have been explored [11][12][13][14][15][16]. Complexes derived from Schiff-base ligands emerged as efficient catalysts for the polymerization of α-olefins [17][18][19][20][21], and their use in the production of biodegradable polymers has been receiving growing interest.…”
Section: Introductionmentioning
confidence: 99%